Influence of Environmental Factors and Impact on Financing Innovation of SMEs - SHAKEYEV, Sayan; DARIBEKOV, Serik; MUTALIYEVA, Lyailya; KHISHAUYEVA, Zhanat; KIZIMBAYEVA, Azhar (Journal of Environmental Management and Tourism, 2021)
The article is devoted to the development and financing of innovations of small and medium-sized enterprises (SMEs) in the Republic of Kazakhstan, which is recognized in the world as an effective lever for ensuring the country's economic growth, since the main part of Kazakhstan's budget revenues is tax revenues from businesses and citizens: it is through them that expenses are financed state (along with borrowed funds). Particular attention is paid to the creation of SMEs around new innovative enterprises using various types of business cooperation and areas of activity in the field of ecology.